2017
DOI: 10.1002/clc.22696
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Effectiveness of Remote Cardiac Monitoring With theCardioMEMSHeart Failure System

Abstract: Heart failure (HF) is a leading cause of cardiovascular mortality in the United States and presents a substantial economic burden. A recently approved implantable wireless pulmonary artery pressure remote monitor, the CardioMEMS HF System, has been shown to be effective in reducing hospitalizations among New York Heart Association (NYHA) class III HF patients. The objective of this study was to estimate the cost‐effectiveness of this remote monitoring technology compared to standard of care treatment for HF. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 48 publications
0
74
0
3
Order By: Relevance
“…The recent CardioMEMS postapproval study showed an even greater decrease of 58% in heart failure hospitalizations at 1-year postimplantation [8] while a recent single-center study showed nearly an 80% reduction in heart failure admission and an almost 70% reduction in overall admissions [9]. Consequently, CardioMEMS has become an economically efficient technology, with the cost of device implantation being under $20,000 [1]. In contrast, using the 5-year observational period following the CHAMPION trial, heart failure treatment costs total nearly $170,000 which include future hospitalizations, monthly monitoring, and routine care and "… all costs are weighted based on the assumption that 75% of patients are covered by Medicare and 25% have commercial coverage" [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent CardioMEMS postapproval study showed an even greater decrease of 58% in heart failure hospitalizations at 1-year postimplantation [8] while a recent single-center study showed nearly an 80% reduction in heart failure admission and an almost 70% reduction in overall admissions [9]. Consequently, CardioMEMS has become an economically efficient technology, with the cost of device implantation being under $20,000 [1]. In contrast, using the 5-year observational period following the CHAMPION trial, heart failure treatment costs total nearly $170,000 which include future hospitalizations, monthly monitoring, and routine care and "… all costs are weighted based on the assumption that 75% of patients are covered by Medicare and 25% have commercial coverage" [1].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, CardioMEMS has become an economically efficient technology, with the cost of device implantation being under $20,000 [1]. In contrast, using the 5-year observational period following the CHAMPION trial, heart failure treatment costs total nearly $170,000 which include future hospitalizations, monthly monitoring, and routine care and "… all costs are weighted based on the assumption that 75% of patients are covered by Medicare and 25% have commercial coverage" [1]. As the technology becomes more widespread, it is important for providers to be aware of the adverse events associated with the device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CHAMPION trial showed not only an improvement in the quality of life but also a reduction in heart failure hospital admissions and a decreased length of admission [ 3 ]. Furthermore, there was a $7,433 six-month comprehensive heart failure cost reduction associated with the lower rate of hospitalizations [ 16 ], and the remote pulmonary artery pressure-monitoring device was also noted to have a cost-effectiveness ratio of $44,832 per quality-adjusted life year [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“… 7 In another study, the CardioMEMS device was found to have a cost-effectiveness ratio of $44,832 per quality-adjusted life year. 8 Elevated diastolic PA pressure is associated with a high risk of hospitalization and mortality, and patients with implantable hemodynamic technology were found to have lower PA pressures. 9 In this study, we sought to identify potential lifestyle changes of patients with CardioMEMS device placement and whether such a technologically advanced device is easy to use for patients.…”
Section: Introductionmentioning
confidence: 99%